2022
DOI: 10.1039/d1gc03907e
|View full text |Cite
|
Sign up to set email alerts
|

Methanol as the C1 source: redox coupling of nitrobenzenes and alcohols for the synthesis of benzimidazoles

Abstract: We present an operationally simple redox coupling for the synthesis of N-1 substituted benzimidazole using feedstock building block 2-nitroaniline derivatives as the precursors and methanol as the C1 source. Higher...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 59 publications
1
5
0
Order By: Relevance
“…The physical and spectral data were consistent with those previously reported. The physical and spectral data were consistent with those previously reported …”
Section: Methodssupporting
confidence: 91%
“…The physical and spectral data were consistent with those previously reported. The physical and spectral data were consistent with those previously reported …”
Section: Methodssupporting
confidence: 91%
“…Recently, Nguyen et al reported an unbalanced redox condensation between o-nitroanilines and benzyl alcohols leading to benzimidazoles by using an iron-sulfur system under solvent-free conditions (Scheme 29a); 55 Li et al described a transfer of hydrogen and successive cyclization coupling reaction from o-nitroanilines and alcohols to furnish benzimidazoles using the Cu-Pd/γ-Al 2 O 3 catalytic system (Scheme 29b); 56 Wang et al developed an efficient synthesis of benzimidazoles from o-nitroanilines and alcohols via a recycled palladium-catalyzed hydrogen-transfer strategy (Scheme 29c); 57 An et al achieved an operationally simple redox coupling for the construction of benzimidazoles using 2-nitroaniline as the amino source and methanol as the carbon source under the Fe-NH 4 Cl catalytic system (Scheme 29d). 58 In 2020, Chen et al developed novel and efficient Co@NC 900 catalysts (Co nanoparticles (NPs) encapsulated in N-doped carbon nanotubes), which were investigated as a potential alternative to precious Pt-group catalysts, catalyzed hydrogenative coupling of 2-nitroaniline with benzaldehyde to construct benzoxazoles with >99% yield (Scheme 30). 59 Additionally, the Co@NC 900 catalysts can be recovered and recycled several times without any evident decrease in the activity.…”
Section: Synthesis Of Benzimidazole Derivativesmentioning
confidence: 99%
“…Recently, Nguyen et al reported an unbalanced redox condensation between o -nitroanilines and benzyl alcohols leading to benzimidazoles by using an iron-sulfur system under solvent-free conditions (Scheme 29a); 55 Li et al described a transfer of hydrogen and successive cyclization coupling reaction from o -nitroanilines and alcohols to furnish benzimidazoles using the Cu–Pd/γ-Al 2 O 3 catalytic system (Scheme 29b); 56 Wang et al developed an efficient synthesis of benzimidazoles from o -nitroanilines and alcohols via a recycled palladium-catalyzed hydrogen-transfer strategy (Scheme 29c); 57 An et al achieved an operationally simple redox coupling for the construction of benzimidazoles using 2-nitroaniline as the amino source and methanol as the carbon source under the Fe-NH 4 Cl catalytic system (Scheme 29d). 58…”
Section: Synthesis Of 5-membered N-heterocyclesmentioning
confidence: 99%
“…The authors have cited additional references within the Supporting Information. [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]…”
Section: Supporting Informationmentioning
confidence: 99%